Effects of different cadmium levels on the growth and yield parameters of wild „Vigna” - Beckley IKHAJIAGBE; Geoffrey Obinna ANOLIEFO; Edokpolor O. OHANMU; Ephraim ALIU (Studia Universitatis Babeș-Bolyai. Biologia)
The assessment of growth and yield parameters of wild vigna to to different levels ofcadmium pollution has been investigated in this study. The experimental setup consisted of three (3) treatments namely; 0, 2.5 and 5 ecological screening value (ESV) and parameters recorded were taken 84 days and 20 weeks namely; plant germination factors,  plant yield, percentage  chlorosis, necrosis and senesced leaves, plant dry matter accumulation as well as plant lifetime morphological changes. Cadmium concentration increased the percentage of foliar chlorosis and necrosis (20.40) in older leaves than younger leaves (4.08) respectively of TVNu-91 sown in 5 ESV cadmium soil and this eventually resulted to an increase in percentage senesced leave with increasing cadmium concentration. Leaf folding and curling symptoms were cadmium-associated in the intermediate partition but same cannot be said for the young plant (YP). However, leaf curling was reported as a prominent morphological feature in this study. With respect to insect foraging, there was total absence of foraging in both control accessions and cadmium polluted accessions. There was also a significant difference (P>0.05) in the number of pods per plant as evidenced in TVNu-95 (5ESV) 5.67 when compared to 14.07 in the control of TVNu-95. Thus, there was a gradual decrease with increasing ecological screening value. Generally, there was significant difference in the seed number per pods (P<0.01), seed weight per pods (P<0.01) plant yield (P<0.01), and flower bud size (P<0.05). 20 weeks after sowing, plant dry matter accumulation was reduced with increase in metal concentration. There was variability in plant yield response to metal toxicity with a general decrease reported with increased cadmium concentration. However, TVNu-93 had a better yield as compared to the other studied accessions.